Nutritional status between 5‐10 years is associated with cystic fibrosis‐related diabetes in adolescence. Issue 10 (28th July 2021) - Ararat, Erhan; Sonawalla, Ambreen; Berlinski, Ariel; Tas, Emir
Abstract: Background: Cystic fibrosis‐related diabetes (CFRD) is a risk factor for adverse clinical outcomes including poor nutritional status, deterioration in lung functions, and increased mortality. The association between nutritional status between 5 and 10 years of age and later diagnosis of CFRD is not known. Methods: A retrospective chart review was performed for our patients with CF between 10 and 18 years. Data was collected at age 5 and 10 years. Comparison made between patients with and without CFRD. Results: Two groups were comparable for age and sex. At age 5, groups had no differences in weight, height, and body mass index. At age 10, the CFRD group had a lower body mass index (40.2 ± 24.7 vs. 61.5 ± 22.5 percentile, p = 0.02). Spirometry was similar between groups at 5 and 10 years. Patients with CFRD had lower growth velocity (5 ± 0.9 vs. 5.7 ± 0.9 cm/year, p = 0.03) and reduced weight gain rate (2.2 ± 0.9 vs. 3.2 ± 1.2 kg/year, p = 0.03) compared to patients without CFRD between 5 and 10 years. Patients with a weight gain less than 2.5 kg/year between 5 and 10 years were nine times more likely to develop CFRD in adolescence (Unadjusted Odds Ratio: 8.9; 95% CI:1.4, 47.2; p = 0.01). Conclusion: Patients who later developed CFRD had significantly lower weight gain rate and height growth between 5 and 10 years of age than those without diabetes. Close monitoring of nutritional status in before age 10 years may help identify CF patients at‐risk of developing CFRD.